Abrahamic religions: on the uses and abuses of history - Hughes, Aaron W. (Oxford University Press, 2013)
Aaron Hughes examines the creation and dissemination of 'Abrahamic religions'. Part genealogical and part analytical his study seeks to raise and answer questions about the appropriateness and usefulness of employing these religions as a vehicle for understanding and classifying data.